2007
DOI: 10.1128/aac.01054-06
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Streptococcus pyogenes Isolates Displaying the MLS B Phenotype of Macrolide Resistance in Spain, 1999 to 2005

Abstract: The aim of this study was to describe the genetic characteristics of Streptococcus pyogenes showing the MLS B phenotype of macrolide resistance from 1999 to 2005 in Spain and to highlight the substantial increase in these isolates in the last few years. The antimicrobial susceptibilities of 17,232 group A streptococci isolated from Madrid and Gipuzkoa from 1999 to 2005 were studied. The presence of the resistance genes ermA, ermB, mef, tetM, and tetO and the presence of the intTn and xis genes of the Tn916-Tn1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 32 publications
5
63
2
Order By: Relevance
“…Some countries have a high proportion of mefA-positive isolates, whereas in other countries, erm genes dominate, leading to higher levels of clindamycin resistance. There is also temporal variation in the distribution of the mefAencoded and erm-encoded phenotypes within the same geographic region (496)(497)(498)(499)(500). Studies in Finland, Spain, and Italy have shown a strong correlation between macrolide usage and resistance of GAS (501)(502)(503).…”
Section: Resistance To Macrolidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries have a high proportion of mefA-positive isolates, whereas in other countries, erm genes dominate, leading to higher levels of clindamycin resistance. There is also temporal variation in the distribution of the mefAencoded and erm-encoded phenotypes within the same geographic region (496)(497)(498)(499)(500). Studies in Finland, Spain, and Italy have shown a strong correlation between macrolide usage and resistance of GAS (501)(502)(503).…”
Section: Resistance To Macrolidesmentioning
confidence: 99%
“…Studies in Finland, Spain, and Italy have shown a strong correlation between macrolide usage and resistance of GAS (501)(502)(503). A rapid increase in the percentage of macrolide-resistant strains may also be due to the clonal expansion of a single resistant strain (442,498,504). Many countries have instituted a more restrictive use of macrolides in response to alarming reports of high rates of macrolide resistance among GAS strains.…”
Section: Resistance To Macrolidesmentioning
confidence: 99%
“…Briefly, typed streptococci were cultured on Columbia agar base medium (Oxoid U.K.) supplemented with 7% sheep blood. The plates were then incubated at 35-37°C for 48hours and typical hemolytic pattern were identified as complete (β-hemolytic), partial (α-hemolytic) and non-hemolytic (Gamma, γ-haemolysis) (Perez-Trallero et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Biotyping: Each identified streptococcus isolates was further biotyped into Lancefield groups according to protocol described by Perez-Trallero et al (2007).…”
Section: 11mentioning
confidence: 99%
“…Phenotypes of macrolide resistance were observed with a double disk synergy test for the ERY-resistant strains. The macrolide resistance genes were determined by PCR using the primers reported elsewhere [9]. …”
Section: Antimicrobial Resistancementioning
confidence: 99%